Experimental demonstration of deformable reflector antenna system with high accuracy deformation measurement. (May 2022) - Tanaka, Hiroaki; Kogiso, Nozomu; Sakano, Fumika; Katsumata, Nobuhisa; Yamazaki, Kenji; Higuchi, Ken; Ishimura, Kosei; Iwasa, Takashi; Kishimoto, Naoko; Fujigaki, Motoharu; Doi, Akihiro; Nakahara, Satomi; et al.
Abstract: In this study, an engineering model for a high-precision reflector antenna system equipped with a deformable sub-reflector with six actuators and a two-dimensional (2D) grating measurement system was developed. In this system, the deformation of the main reflector of the antenna system was measured by a 2D grating measurement system. Then, the path length error due to the deformation was compensated by adjusting the shape of the deformable sub-reflector. A novel path length error correction procedure for obtaining shape control inputs was also developed. With this method, the antenna deformations of the entire reflector area were estimated from the measured deformations at limited measurement points to decrease the measurement durations. An experiment was carried out to investigate the effectiveness of the developed system and the limitation of the deformable reflector with a small number of actuators. In the experiment, the main reflector was intentionally deformed by applying a load. The changes in the power of radio waves received from a satellite were measured during the experiments, and the effectiveness of the developed system was investigated. The deteriorated reception power due to the deformation of the main reflector was recovered to some extent using the deformable reflector. Thus, the findings demonstrated the effectiveness of the developed smart reflector antenna system and also indicated the limitation caused by the difference between the deformation shapes of the main reflector and the deformable reflector. Highlights: Prototype of the deformable reflector antenna system with high accuracy deformation measurement was developed and its effectiveness were investigated through experimental demonstration. The deformation of the main reflector was measured using the two-dimensional grating measurement system, and the path length error due to the deformation was compensated by the deformable sub-reflector. New procedure for path length compensation was developed. In this method, the antenna deformations of the entire reflector area were estimated from the measured deformations at a small number of measurement points to decrease the measurement durations. The effectiveness and limitation of the path length error compensation by the developed smart reflector system was demonstrated through the experiments.